Transcriptome analysis in hepatopancreases reveals the response of domesticated common carp to a high-temperature environment in the agricultural heritage rice–fish system - Cheng, Xiangbing; Li, Fangcheng; Kumilamba, Gilbert; Liao, Jiayi; Cao, Jiangwei; Sun, Jiamin; Liu, Qigen (Frontiers in Physiology, 2023)
Qingtian paddy field carp (PF-carp) is a local carp cultivated in the paddy field of Qingtian, Zhejiang. This rice-fish coculture system has been recognized as a Global Important Agriculture Heritage System (GIAHS). PF-carp has been acclimatized to the high temperature environment of shallow paddy field after a several centuries of domestication. To reveal the physiological and molecular regulatory mechanisms of PF-carp, we chose to use 28 ℃ as the control group and 34 ℃ as the treatment group. We measured biochemical parameters in their serum and hepatopancreases, and also performed transcriptome sequencing analysis. Compared with control group, MDA, GLU, GSH-Px, CAT, ALT and AST has no significantly change in serum. And SOD, GSH-Px and CAT also has no significantly change in hepatopancreases. We identified 1253 differentially expressed genes (DEGs) and their pathways analysis revealed that heat stress affected AMPK signaling pathway, protein export, and other biological processes. It is worth noting that protein processing in the endoplasmic reticulum was the most significantly enriched by KEGG and GSEA enrichment analysis. Significantly higher levels of HSP40, HSP70, HSP90 and other ubiquitin ligase-related genes which were up-regulated. In summary, heat stress did not lead to tissue damage, inflammation, oxidative stress and endoplasmic reticulum (ER) stress in the hepatopancreases of PF-carp. This study provides valuable insights into how this species adapts to high temperature environment in paddy field.